(untitled) (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2025)
Abstract This study aims to determine the interaction in the provision of chicken manure and Growmore leaf fertilizer, and to obtain the dose that can provide the best effect on the growth and yield of Scallion Plants (Allium fistulosum L.) Jafra Variety. This study was conducted in Cirawa Village, Cibeureum Village, Kertasari District, Bandung Regency, West Java Province. The altitude of the place is ± 1500 m above sea level, with rainfall of 2354.2 mm/year, including rainfall of the C3 agroclimate type according to Oldeman. The research used an experimental method that was conducted in a Randomized Block Design with factorial treatments and replicated 3 times. Factor I: chicken manure (k1 = control, k2 = 15 tons/ha, k3 = 30 tons/ha). Factor II: Growmore leaf fertilizer (g1 = control, g2 = 2 grams/l, g3 = 4 grams/l). The results showed that there was no interaction between the provision of chicken manure and Growmore leaf fertilizer on the growth and yield of scallion plants. The independent effect of giving 30 tons/ha of chicken manure fertilizer gave a better and significantly different effect on the height of the plant, the weight of the green onions per planting and the weight of the green onions per plot of the Jafra variety. Abstrak Penelitian ini bertujuan untuk mengetahui interaksi dalam pemberian pupuk kandang ayam dan pupuk daun Growmore, serta untuk memperoleh dosis yang dapat memberikan pengaruh paling baik terhadap pertumbuhan dan hasil Tanaman Bawang Daun (Allium fistulosum L.) Varietas Jafra. Penelitian ini dilaksanakan di Kampung Cirawa, Desa Cibeureum, Kecamatan Kertasari, Kabupaten Bandung, Provinsi Jawa Barat. Ketinggian tempat ± 1500 m di atas permukaan laut, Dengan curah hujan 2354,2 mm/tahun termasuk curah hujan tipe agroklimat C3 menurut Oldeman. Penelitian ini menggunakan metode Rancangan Acak Kelompok (RAK) pola faktorial dengan 3 kali ulangan. Faktor I: pupuk kandang ayam (k1= kontrol, k2= 15 ton/ha, k3= 30 ton/ha). Faktor II: Pupuk daun Growmore (g1= kontrol, g2= 2 gram/l, g3= 4 gram/l). Hasil penelitian menunjukan bahwa tidak terjadi interaksi antar pemberian pupuk kandang ayam dan pupuk daun Growmore terhadap pertumbuhan dan hasil tanaman bawang daun. Pengaruh mandiri pemberian pupuk kandang ayam 30 ton/ha memberikan pengaruh yang lebih baik dan berbeda nyata terhadap bobot bawang daun pertanaman dan bobot bawang daun perplot varietas Jafra. Kata kunci : bawang daun, dosis, hasil, growmore, kandang ayam